Reaction of lake environment on the climatic cooling – Transition from the Eemian Interglacial to Early Vistulian on the basis of Solniki palaeolake sediments (NE Poland). (2nd November 2015) - Mirosław-Grabowska, Joanna; Niska, Monika; Kupryjanowicz, Mirosława
Abstract: Results of Cladocera and organic matter analyses from the Eemian lake deposits in Solniki (NE Poland) are presented. We focused on the reaction of the lake's environment to progressive cooling reflected in the changes of the organic matter and the Cladocera community. Approximately 3-m of sediments accumulated from the optimum of the Eemian Interglacial (E5) to the Early Vistulian (EV2) were analyzed. Results of analyses of organic matter correlated with Cladocera data enabled a reconstruction of varying environmental conditions and geneses of organic matter. The organic carbon content is closely related to climatic conditions. The lowest values are recorded in the coldest periods during the ending of the Eemian Interglacial and the Herning stadial of the Early Vistulian. The highest ones occur unexpectedly in the Eemian post-optimum: at the end of the spruce phase and at the beginning of the pine phase. During the Eemian optimum (E5), biodiversity of Cladocera species was maximal (17), but the frequency of specimens was low. At the end of the optimum (E5), an improvement of living conditions, more optimal for various ecological groups of Cladocera took place. Algae remained a significant component of organic matter. The early Eemian post-optimum (E6) is characterized as a period of the high number of zooplankton species, the highest frequency as well as biodiversity. At that time, probably a higher water level and an optimal temperature formed very favorable conditions for the fauna development. During this period, maximal values of TOC, TN and the slight increase of C/N ratio suggest a higher primary productivity with a small supply of organic matter of terrestrial origin. Coexistence of two species of the family Bosminidae and maximum values of δ 15 N suggest a high trophy (β-mesotrophy). High resolution and detailed analyses of the lake sediments accumulated during the pollen zone E7, allowed to identity a few minor environmental fluctuations recorded in varied Cladocera frequency, TOC and C/N ratio. In the final period of the Eemian Interglacial and in the Early Vistulian (Herning stadial), a drastic reduction in frequency of Cladocera and the features of OM (the lowest amounts of TOC and TN, and the highest value of C/N) reflect the decline of lake conditions and a lack of both primary production and aquatic vegetation in the lake. During the Amersfoort interstadial a renewed bioproduction and slightly supply of terrestrial plants in organic matter as well as revitalize zooplankton took place.